2012
DOI: 10.1371/journal.pone.0051981
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Carriage of ESBL-Producing E. coli and K. pneumoniae in Children in Guinea-Bissau: A Hospital-Based Cross-Sectional Study

Abstract: BackgroundIn recent years, the world has seen a surge in extended-spectrum β-lactamase (ESBL)-producing bacteria. However, data on the dissemination of ESBL-producing Enterobacteriaceae in the community from systematically enrolled study subjects in Africa remains limited. To determine the prevalence, phenotypic resistance patterns and genetic characteristics of ESBL-producing E. coli and K. pneumoniae in fecal carriage and to analyze associated risk factors in children attending a pediatric emergency departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
73
8
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 34 publications
20
73
8
3
Order By: Relevance
“…Our results disagree with many studies all over the world that reported bla CTX-M was the predominant gene among ESBL-producing E. coli isolated from fecal samples of healthy subjects [4,23,24], which may be explained by the variability in resistance patterns and encoding genes according to different geographic regions.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results disagree with many studies all over the world that reported bla CTX-M was the predominant gene among ESBL-producing E. coli isolated from fecal samples of healthy subjects [4,23,24], which may be explained by the variability in resistance patterns and encoding genes according to different geographic regions.…”
Section: Discussioncontrasting
confidence: 99%
“…Most of the isolates in the present study were resistant to multiple antibiotic groups. High resistance to common antibiotics has also been reported in previous studies [7,11,26]. The present study offers the first characterization of TEM-type and SHV-type ESBL variants produced by E. coli circulating in hospitals in Hamadan (northwest Iran).…”
Section: Discussionsupporting
confidence: 77%
“…Isendahl et al [11] reported that 32.6% fecal samples from children were carriers of ESBLproducing E. coli or K. pneumonia. Shahid et al [22] reported findings similar to those of the present study: 38.4% of the isolates in their study were positive for bla genes, and the bla TEM gene was more prevalent than the bla SHV gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Es importante mencionar que en los últimos años se ha descrito el incremento de enterobacterias productoras de BLEE de la familia CTX-M (19) , en este estudio se encontró que la gran mayoría de los aislados productores de BLEE presentaban en gen bla CTX-M, el grupo de gen dominante en los estudios de portadores fecales de República Checa (15) , España (20) , India (2) , Madagascar (16) , Nigeria (17) , Francia (24) , Guinea-Bissau (25) y Japón (26) poniendo de relieve la importancia de este gen en la difusión global de BLEE. La BLEE tipo CTX-M tiene principalmente actividad sobre la cefotaxima y no sobre la ceftazidima; aunque en los últimos años la emergencia de variantes de CTX-M (CTX-M-15, CTX-M-16, CTX-M-27 y CTX-M-19) están mejorando su actividad frente a ceftazidima.…”
Section: Discussionunclassified